2016
DOI: 10.1007/s12517-015-2303-8
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variability of the rainfall erosivity factor in Northern Algeria

Abstract: Erosion, sediment transport, and deposition result in agricultural soil degradation, dam siltation, and significant and costly damage. In Algeria, despite a decrease in total rainfall, especially in the central and western parts of the country, dam siltation and erosion are on the rise according to recent studies by the National Agency of Dams and Transfers. Developing a map of the spatial variation of rainfall erosivity will provide a powerful tool for land and dam managers. Erosivity can be quantified using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…In addition to a point estimate of the R factor, a spatial information (map) is often required for practical purposes. A number of such maps have been released recently at national (Lu and Yu, 2002;Yin et al, 2007;Bonilla and Vidal, 2011;Oliveira et al, 2013;Borrelli et al, 2016;Panagos et al, 2016a;Meddi et al, 2016) or larger (Panagos et al, 2015) scales.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to a point estimate of the R factor, a spatial information (map) is often required for practical purposes. A number of such maps have been released recently at national (Lu and Yu, 2002;Yin et al, 2007;Bonilla and Vidal, 2011;Oliveira et al, 2013;Borrelli et al, 2016;Panagos et al, 2016a;Meddi et al, 2016) or larger (Panagos et al, 2015) scales.…”
Section: Introductionmentioning
confidence: 99%
“…Afterward, rainfall and R-factor were mapped by means regression-kriging (Meusburger et al, 2012;Mello et al, 2013;Oliver and Webster, 2014;Borrelli et al, 2016;Meddi et al, 2016), with the aid of the Geographical Information System ArcGIS. In this procedure, the altitude extracted from the SRTM elevation digital model was used, and rainfall and R-factor maps were made under format raster, with 90-meter spatial resolution, using the models.…”
Section: Rainfall and R-factor Mapping Based On Regression-krigingmentioning
confidence: 99%
“…Both studies concluded that, because of the physical-environmental elements being highly and naturally variable, the models may be applied. Meddi et al (2016) incorporated longitude and altitude into the modeling of rainfall erosivity in Argelia, reporting the great importance of longitude as an explanatory variable for rainfall erosivity in that place. In the present study, the coefficients of determination were comparable to the above-mentioned studies and can be rated as good quality; especially considering that the state of Tocantins is located within a climatic transition region between the biomes of Cerrado and Amazon.…”
Section: Mapping Of Average Rainfall and R-factor For The State Of Tomentioning
confidence: 99%
“…During the last 30 years the Revised Universal Soil Loss Equation (RUSLE) [RENARD et al 1997;WISCHMEIER, SMITH 1978] was applied widely by hydrologist for predicting erosion risk in Africa [ADE- DIJI et al 2010;ANGIMA et al 2003;ANYS 1991;ANYS et al 1994;BENKADJA et al 2015;BONN 1998;CHEN et al 2008;FAGBOHUN et al 2016;LIGONJA, SHRESTHA 2013;MATI, VEIHE 2001;MEDDI et al 2016;SMITH 1999]. In this paper, the RUSLE model was applied to quantify soil losses and to map erosion prone areas in the Hammam Debagh watershed.…”
Section: Introductionmentioning
confidence: 99%